Pengaruh Human Capital Dan Kepuasan Kerja Terhadap Kinerja Karyawan Di Universitas Matana - Yangid Fanggidae, Paulus (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
In this study an analysis of primary data was collected using a questionnaire with the sample being all academic and non-academic employees at Matana University. The data were processed using statistical methods using SPSS and calculations using numerical methods. The relationship and its influence uses the multiple regression method where Human Capital and Job Satisfaction as independent variables have a significant and positive influence on performance, amounting to 51.65% and the remaining 48.35% is influenced by other variables, Human Capital and Kingdom Satisfaction have a strong correlation to Performance which is equal to 0.7295.